1999
DOI: 10.3109/13550289909021286
|View full text |Cite
|
Sign up to set email alerts
|

Immunobiology of the blood-brain barrier

Abstract: The brain microvessel endothelial cells (BMVEC) that form the blood-brain barrier are uniquely positioned to in¯uence immune responses within the central nervous system. As the biological interface separating the blood from the brain extracellular¯uid, BMVEC regulate the entry of leukocytes into the brain. In addition, through the release of various soluble factors that affect immune responses, BMVEC may modulate immune responses in the brain. This review addresses the interplay between the immune system and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(66 citation statements)
references
References 58 publications
1
63
0
2
Order By: Relevance
“…In vivo, the BBB is a dynamic and integrated structure in which brain endothelial cells are intimately associated with other cell types, including pericytes, perivascular macrophages, and astrocytic foot processes (54). In prior work, we found that the addition of astrocyte-conditioned medium to HBECs decreased the permeability of soluble molecules across this barrier, but did not affect cellular migration (55).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, the BBB is a dynamic and integrated structure in which brain endothelial cells are intimately associated with other cell types, including pericytes, perivascular macrophages, and astrocytic foot processes (54). In prior work, we found that the addition of astrocyte-conditioned medium to HBECs decreased the permeability of soluble molecules across this barrier, but did not affect cellular migration (55).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the endothelium serves as a selective permeability barrier between the blood and tissue, including the brain (Albert et al 1997), and produces a variety of growth factors and peptide hormones ( Miller 1999, Vapaatalo & Mervaala 2001. While multiple signaling pathways impact on these diverse end points, many of these diverse cell functions including nitric oxide (NO) production by endothelial NO synthase (eNOS) and prostanoid production in response to cytosolic phospholipase A2 activation are thought to be mediated by Ca 2C signaling.…”
Section: Introductionmentioning
confidence: 99%
“…Brain endothelial cells and immune cells activated by cytokines or infection overexpress adhesion molecules and their ligands, promoting the binding of circulating immune cells to brain vasculature (36). Such binding could be the first step in diapedesis, the passage of immune cells across the BBB (44). This close proximity could also facilitate the passage of virus between the infected immune cell and the brain endothelial cell, analogous to the transfer of virus between infected immune cells and epithelial cells (14).…”
mentioning
confidence: 99%